K. Marx’s Teaching – Basis for Our Investigations (Review of the Republican Scientific Conference of Philosophers) - Kalenda, Česlovas (Problemos, 1968)
A review of materials presented at the scientific conference of philosophers is given in the article. The conference, devoted to the 150th anniversary of K. Marx’s birth, was held in the Vilnius V. Kapsukas State University in 1968. The author of the article presents the main problems of the reports, raises the idea of methodological importance of K. Marx’s teaching in modern times. At the conference K. Marx’s views on the contents of social revolution were investigated, utopian tendencies in modern theory and practice were criticized (the speaker E. Meškauskas), the place of the alienation problem in Marxist sociological conception was shown (the speaker J. Repšys), the formation of atheistic and scientific materialistic views of K. Marx was spoken about (the speakers I. Zaksas, A. Griška, and E. Krakauskas), questions of the social equality of women (the speaker F. Škliarskaitė), methodological problems of investigation of family relations (the speaker N. Solovjev) and many other questions were analysed.